Influence of different fertility levels on yield and nutrient status in zero till direct-seeded rice cultivation - Birendra Kumar; Ram Swaroop Meena; Supriya; Rakesh kumar; Amresh Chaudhary; Ganesh Patel (Journal of Cereal Research, 2024)
The conventional methods, along with excessive fertilizer application in the rice-wheat cropping system, commonly result in decreased productivity and environmental pollution. However, employing zero tillage methods that involve retaining surface residues, alongside strategic nutrient management, could potentially enhance productivity and the efficient utilization of water and nutrients in zero-till direct-seeded rice (ZTDSR). Keeping this in mind, the present investigation was conducted at the Agriculture Research Farm, Institute of Agricultural Sciences, Banaras Hindu University, Varanasi, Uttar Pradesh, India during kharif season of 2019-20. The experiment was conducted in Randomised Block Design with four replication and five different nutrient treatment viz., control, 75 % RDF+5 Kg Fe+5 Kg Zn, 100% RDF, 100 % RDF+5Kg Fe+5Kg Zn and 125 % RDF. Urea, diammonium phosphate (DAP), muriate of potash (MOP), Iron sulphate and zinc sulphate were used as source of nitrogen, phosphorus, potassium, iron and zinc. The rice varieties HUR-105 was used as the rate of 30 kg/ha. The application of 100% RDF+ Zn 5kg/ha+ Fe5kg/ha significantly enhanced the yield, nutrient content and uptake in ZT-DSR.